Fusion-Independent Satellite Cell Communication to Muscle Fibers During Load-Induced Hypertrophy. Issue 1 (6th July 2020) - Murach, Kevin A; Vechetti, Ivan J; Van Pelt, Douglas W; Crow, Samuel E; Dungan, Cory M; Figueiredo, Vandre C; Kosmac, Kate; Fu, Xu; Richards, Christopher I; Fry, Christopher S; McCarthy, John J; Peterson, Charlotte A
Abstract: The "canonical" function of Pax7+ muscle stem cells (satellite cells) during hypertrophic growth of adult muscle fibers is myonuclear donation via fusion to support increased transcriptional output. In recent years, however, emerging evidence suggests that satellite cells play an important secretory role in promoting load-mediated growth. Utilizing genetically modified mouse models of delayed satellite cell fusion and in vivo extracellular vesicle (EV) tracking, we provide evidence for satellite cell communication to muscle fibers during hypertrophy. Myogenic progenitor cell-EV-mediated communication to myotubes in vitro influences extracellular matrix (ECM)-related gene expression, which is congruent with in vivo overload experiments involving satellite cell depletion, as well as in silico analyses. Satellite cell-derived EVs can transfer a Cre-induced, cytoplasmic-localized fluorescent reporter to muscle cells as well as microRNAs that regulate ECM genes such as matrix metalloproteinase 9 ( Mmp9 ), which may facilitate growth. Delayed satellite cell fusion did not limit long-term load-induced muscle hypertrophy indicating that early fusion-independent communication from satellite cells to muscle fibers is an underappreciated aspect of satellite cell biology. We cannot exclude the possibility that satellite cell-mediated myonuclear accretion is necessary to maintain prolonged growth, specifically in the later phases of adaptation, but these data collectively highlight how EV delivery from satellite cells can directly contribute to mechanical load-induced muscle fiber hypertrophy, independent of cell fusion to the fiber. Graphical Abstract: